Coastal upwelling affects filter-feeder stable isotope composition across three continents. (May 2019) - Puccinelli, Eleonora; McQuaid, Christopher D.; Dobretsov, Sergey; Christofoletti, Ronaldo A.
Abstract: Large-scale nutrient fertilisation by coastal upwelling promotes benthic productivity through energy subsidies from enhanced phytoplankton production, and predictions of alterations to upwelling under climate change have implications for benthic ecosystem functioning. We investigated the stable isotope compositions of two bioengineers of global significance, the mussels Perna perna and Mytilus galloprovincialis, from upwelling and non-upwelling sites in five upwelling systems. Samples from Brazil, South Africa and Oman exhibited lower δ 13 C values at upwelling sites than at non-upwelling sites, with clearer effects where upwelling is more intense and frequent. North West Africa showed variability, probably linked to Saharan dust input. We highlight the importance of upwelling to sustaining benthic primary consumers and the sensitivity of consumer diet to the intensity and frequency of upwelling within each region. These results have implications in relation to climate change scenario effects on upwelling events, with potential cascading effects on higher trophic levels and ecosystem functioning. Highlights: We examined upwelling effects on bioengineer diets in five upwelling systems. Filter feeder δ 15 N was not influenced by upwelling. Mussel δ 13 C at upwelling sites was lower than at non-upwelling sites in four regions. Variation in North Africa reflected possible additional effects of Saharan dust input. The effects of upwelling were nested within system-specific factors.